1995
DOI: 10.1111/j.1365-2486.1995.tb00034.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of elevated CO2concentrations on the root growth of Lolium perenne and Trifolium repens grown in a FACE* system

Abstract: Lolium perenne and Trifolium repens were grown in a Free Air CO2 Enrichment (FACE) system at elevated (600 }.imol mol"*) and ambient (340 [jmol mol"^) carbon dioxide concentrations during a whole growing season. Using a root ingrowth bag technique the extent to which CO2 enrichment influenced the growth of L, perenne and T. repens roots under two contrasting nutrient regimes was examined. Root ingrowth bags were inserted for a fixed time into the soil in order to trap roots. It was also possible to follow the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 46 publications
9
70
1
Order By: Relevance
“…In this study, we focused on L. perenne and T. repens mainly to compare our data with other studies performed on the FACE field experiment in Eschikon (Switzerland) [23,25,29,30,42,57,72,74]. Moreover, the plants have different rhizosphere structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we focused on L. perenne and T. repens mainly to compare our data with other studies performed on the FACE field experiment in Eschikon (Switzerland) [23,25,29,30,42,57,72,74]. Moreover, the plants have different rhizosphere structures.…”
Section: Discussionmentioning
confidence: 99%
“…In a prairie ecosystem such as the FACE facility in Eschikon, soil carbon input is mainly the result of dead plants and rhizodeposition. Jongen et al [30] measured in the FACE study site of Eschikon an increased C:N ratio of L. perenne roots grown in monoculture at elevated pCO 2 , while they detected no changes in the C:N ratio of clover roots. From the perspective of microbial numbers, Zak et al [70] suggested that an increased carbon input into the soil could be counterbalanced by an increased C:N ratio, leading to unchanged microbial numbers.…”
Section: Impact Of Elevated Co 2 On Soil Heterotrophic Bacteriamentioning
confidence: 97%
See 1 more Smart Citation
“…Carbohydrate concentrations at elevated Pcon with low N supply were consistently higher than in the other three treatments; this coiToborates the suggestion of a N-dependent sink limitation in plants subjected to that treatment. Plants grown at low N supply had a lower above-ground dry matter yield (Hebeisen et al 1997) and their root mass was larger (Jongen et al 1995;Hebeisen et al 1997); these symptoms strongly suggest nutrient-limited growth and, as a consequence, a possible change in root:shoot allometiy. Such a Ndependent sink limitation was most pronounced in first fully grown leaves.…”
Section: Comparison Of Sources: Leaves and Pseudostemsmentioning
confidence: 99%
“…Therefore, elevated /?co2 '^''^ "o* appear to accelerate metabolic recovery from defoliation in spite of the obvious increase in carbohydrate availability. Instead, the enhanced carbohydrate availability at elevated Pco2 rnay have been matched by a higher sink detnand -possibly as a consequence of the respitatory needs for the maintenance and function of a larger root system (Jongen et al, 1995;Hebeisen et al 1997) as no evidence for an enhanced initial rate of regrowth was observed (F. Stadelmann & T. Hebeisen, unpublished results).…”
Section: Carbohydrate Availability In Source Leavesmentioning
confidence: 99%